2021
DOI: 10.1186/s12905-021-01515-x
|View full text |Cite
|
Sign up to set email alerts
|

Spousal violence against women and its consequences on pregnancy outcomes and reproductive health of women in India

Abstract: Background Globally, one in three women experienced domestic violence. Alike the scenario observed in India, and a very few studies talk about violence and its consequences on women's health. Hence, the purpose of this study is to access the level of various types of spousal violence in India and to understand the association between physical, sexual and emotional violence against ever-married women by their husbands. The study further examines the consequences of spousal violence on women's he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
(36 reference statements)
1
7
0
1
Order By: Relevance
“…It was observed that women with a history of sexual IPV reported a higher risk of having unintended pregnancies, even when the socioeconomic and demographic characteristics of the respondents were controlled for through a hierarchical approach. The said higher odds of unintended pregnancy in victims of sexual violence alone compared to physical violence corroborated with the previous studies from India and abroad [16,24]. Other studies have also demonstrated that sexual IPV alone was the strongest predictor of unintended pregnancies among all forms of IPV [25].…”
Section: Discussionsupporting
confidence: 85%
“…It was observed that women with a history of sexual IPV reported a higher risk of having unintended pregnancies, even when the socioeconomic and demographic characteristics of the respondents were controlled for through a hierarchical approach. The said higher odds of unintended pregnancy in victims of sexual violence alone compared to physical violence corroborated with the previous studies from India and abroad [16,24]. Other studies have also demonstrated that sexual IPV alone was the strongest predictor of unintended pregnancies among all forms of IPV [25].…”
Section: Discussionsupporting
confidence: 85%
“…Although there are studies in the literature examining the causes and consequences of violence against women, no study comparing the perceptions of women who are victims of violence regarding parenting and the desire to avoid pregnancy could be found (Bramhankar & Reshmi, 2021;Ebrahimi & Mohamadlou, 2019;Nnaemeka, Anazodo & Okeke, 2015). In this study, which evaluated the perceptions of married and fertile women who were over the age of doi: 10.33715/inonusaglik.1231583 Women Victims of Violence: A Comparison of Their Perceptions of Parenting and Desire to Avoid Pregnancy Esra GÜNEY, Esra KARATAŞ OKYAY 1117 been exposed to violence, nearly half of the participants (44.1%) stated that they had been subjected to violence.…”
Section: Discussionmentioning
confidence: 99%
“…Norms related to sexuality, masculinity, and marriage put girls at increased risk of sexual and gender-based violence (GBV) ( UN Women, 2020b ; Bramhankar and Reshmi, 2021 ; Kotlar et al, 2021 ; WHO, 2020 ) and early marriage ( UNESCO. UNESCO, 2020 ; UNICEF.…”
Section: Methodsmentioning
confidence: 99%